#TITLE_ALTERNATIVE# - JATI PUTRO (NIM 15104010); Pembimbing: Prof. Dr. Ir. Hasanuddin Z.A., M.Sc., dan Heri Andreas, WIBOWO
In GPS data processing, there is a significant step, that step is constraining data methode to a reference point or a reference frame. The reference point could be a realization of a reference frame such as DGN 95, WGS 84 or ITRF (International Terrestrial Reference Frame) 199X, 200X. The constraining results of a difference reference frame system could be different each other, both in terms of itÃ‚Â’s magnitude and thoroughness. As an example, the output coordinates constrained to DGN 95 is different with the output coordinates constrained with WGS 84 or ITRF 1994 is different with the output coordinates constrained to ITRF 2000 or ITRF 2005. There is possibility happened a variations between it. Theoretically constraining to the ITRF 2005 will provide better results accuracy compared to ITRF 1994, it is due to ITRF 2005 is more stable. The writing of this final task aims to determine the correlation of the use of ITRF series with accuracy obtained. Nets point Lembang fault deformation monitoring will try to be tied to the ITRF 1994, 1996, 1997, 2000, and 2005 and to find out the implications of the use of these tie points to the shift vector in the study of fault system (with the Lembang Fault case study).